A Review on Study Efficiency of Thymus vulgaris L plant Extract on Multidrug Resistance Bacteria - Hamza, Zaman S.; Hussein, Mustafa jaafar; Al-Ajeeli, Zahraa A. Al- (Jour Med Resh and Health Sci, 2023)
Since fewer or occasionally no antimicrobial agents are effective against such bacteria, the global rise of multi-drug resistant bacteria has turned into a health crisis. The objective of the presented work is to determine the antibacterial efficacy of Thymus vulgaris extracts against bacteria that have developed multidrug resistance, including staphylococcus, E. coli, and Klebsiella. T. vulgaris, a prominent aromatic plant with around 100 species worldwide, is frequently utilized both for culinary and medicinal purposes. Becaise of the numerous therapeutic benefits of its essential oils, commonly referred to as thyme oil, the genus Thymus contains significant medicinal herbs that come highly recommended. Because of their biological and pharmacological characteristics, thymus species are regarded as medicinal plants. Its primary ingredients, carvacrol and thymol, are responsible for its characteristics. Among all herbs, fresh thyme possesses the most antioxidants. Thymus vulgaris L. is frequently utilized in folk medicine for treating a wide range of illnesses, including gastro enteric and bronchopulmonary disorders. In vitro tests against Staphylococcus sp., E. coli strains, and Streptococcus pp. revealed antimicrobial activity of thyme essential oil and the compound thymol. Strongest antimicrobial effects have been observed in thyme essential oil.